Trace‐element heterogeneity in rutile linked to dislocation structures: Implications for Zr‐in‐rutile geothermometry. (1st August 2022) - Verberne, Rick; van Schrojenstein Lantman, Hugo W.; Reddy, Steven M.; Alvaro, Matteo; Wallis, David; Fougerouse, Denis; Langone, Antonio; Saxey, David W.; Rickard, William D. A.
Abstract: The trace‐element composition of rutile is commonly used to constrain P – T – t conditions for a wide range of metamorphic systems. However, recent studies have demonstrated the redistribution of trace elements in rutile via high‐diffusivity pathways and dislocation‐impurity associations related to the formation and evolution of microstructures. Here, we investigate trace‐element migration in low‐angle boundaries formed by dislocation creep in rutile within an omphacite vein of the Lago di Cignana unit (Western Alps, Italy). Zr‐in‐rutile thermometry and inclusions of quartz in rutile and of coesite in omphacite constrain the conditions of rutile deformation to around the prograde boundary from high pressure to ultra‐high pressure (~2.7 GPa) at temperatures of 500–565°C. Crystal‐plastic deformation of a large rutile grain results in low‐angle boundaries that generate a total misorientation of ~25°. Dislocations constituting one of these low‐angle boundaries are enriched in common and uncommon trace elements, including Fe and Ca, providing evidence for the diffusion and trapping of trace elements along the dislocation cores. The role of dislocation microstructures as fast‐diffusion pathways must be evaluated when applying high‐resolution analytical procedures as compositional disturbances might lead to erroneous interpretations for Ca and Fe. In contrast, our results indicate a trapping mechanism for Zr.